Structures of self-assembled n-alkanethiols on gold by reflection high-energy electron diffraction. Issue 30 (21st July 2020) - Ghosh, Mithun; Yang, Ding-Shyue
Abstract : The structures of long-chain alkanethiols (C18 H37 SH) chemisorbed on an Au(111) single crystal were investigated using reflection high-energy electron diffraction (RHEED). Abstract : The structures of long-chain alkanethiols (C18 H37 SH) chemisorbed on an Au(111) single crystal were investigated using reflection high-energy electron diffraction (RHEED). The primary structure observed as a major species in the as-deposited films contains gold adatoms below the sulfur headgroups. Between the small ordered domains with the alkyl chains tilting toward six directions are azimuthally disorderly packed regions, with a similar average tilt of 30.2°. In contrast, a significant reduction in the coverage of gold adatoms is found in the thermally-induced phase. This superlattice is shown to contain a mixture of two sulfur arrangements, both of which exhibit a small S–S distance, and the pairing of the aliphatic chains. A microscopic picture is then given for the structural transition. These findings demonstrate how the RHEED technique may be used to resolve structures of nanometer-thick thin films with multiple orders at the interfaces.